Educational robotics. A new challenge for the Panamanian education - Alejandro A. Barranco Candanedo (Ediciones Universidad de Salamanca, 2012)
<!--[if gte mso 9]> Normal.dotm 0 0 1 36 209 Universidad de Salamanca 1 1 256 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> The educational robotics a new challenge for Panamanian education break new ground in the school curriculum, this leads to introduce robotic technology in the classroom, which brings new challenges for teachers and students, who face high expectations. <!--EndFragment-->